2021
DOI: 10.1002/jhet.4221
|View full text |Cite
|
Sign up to set email alerts
|

Aza‐Michael addition of 1,2‐diazoles to structurally diverse enones: Efficient methods toward β‐amino ketones

Abstract: An efficient and mild protocol was realized using 1,2‐diazoles and related heterocycles with cyclic and acyclic enones in presence of T3P (2,4,6‐tripropyl‐1,3,5,2,4,6‐trioxatriphosphorinane‐2,4,6‐trioxide) toward the regioselective formation of N‐cycloalkyl heterocycles at room temperature. The developed reaction conditions showcased good selectivity over a wide range of 1,2‐diazoles and enones by delivering N‐cycloalkyl heterocycles in excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…[20] The successful addition of pyrazoles to five-, sixor seven-membered cyclic and acyclic enones is realized in the presence of 1.1 equivalent of 2,4,6tripropyl-1,3,5,2,4,6-trioxatriphosphorinane-2,4,6-trioxide (T3P) under mild reaction conditions. [21] The aza-Michael reaction proceeds smoothly in good to high yields even for 4-nitro-lH-pyrazole: the corresponding adduct 16 is isolated in 65% yield (Scheme 5). This approach shows an excellent func- tional group tolerance and can be applied to tri-and tetrazoles.…”
Section: Pyrazoles Imidazoles Triazoles and Tetrazolesmentioning
confidence: 99%
“…[20] The successful addition of pyrazoles to five-, sixor seven-membered cyclic and acyclic enones is realized in the presence of 1.1 equivalent of 2,4,6tripropyl-1,3,5,2,4,6-trioxatriphosphorinane-2,4,6-trioxide (T3P) under mild reaction conditions. [21] The aza-Michael reaction proceeds smoothly in good to high yields even for 4-nitro-lH-pyrazole: the corresponding adduct 16 is isolated in 65% yield (Scheme 5). This approach shows an excellent func- tional group tolerance and can be applied to tri-and tetrazoles.…”
Section: Pyrazoles Imidazoles Triazoles and Tetrazolesmentioning
confidence: 99%
“…After establishing the optimized conditions for the envisaged transformation, we focused on proposing a plausible mechanistic pathway under the HMPT-mediated conditions for the synthesis of desired products (Scheme 2). 12,14 The electron pair situated on oxygen atom of enone 1a may participate in nucleophilic attack towards the phosphorus atom of P(NMe2)3 (A), which leading to the formation of expected intermediate B and that may be assumed in the existence of resonance form B′. The reaction between intermediate B′ and azole 2 could deliver the intermediate C, which finally produces the expected molecule 3 followed by consequent hydrolysis of P-O bond and tautomerization process.…”
Section: Conditions A)mentioning
confidence: 99%
“…Recently, a T3P-mediated approach has been described for the reaction of enone-molecules with diverse azoles employing aza-Michael addition protocol at room temperature with good yields and selectivity. 12 Additionally, during the past decades, the greener approaches of Michael-addition reaction have accumulated increasing interest and found enormous application in organic synthesis. [3][4][5]7,11 In this regard, we have designed a new process by utilizing a mild and robust HMPT as reagent for the reaction between enones and azoles at room temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite significant advances in the aza-Michael addition of various heterocycles, most transformations have been limited to acyclic α , β -unsaturated substrates, and only a few studies have reported the synthesis of N -cycloalkyl-substituted β -amino carbonyls from cyclic substrates. 4 Furthermore, the aza-Michael addition of heterocycles to β , β -disubstituted enones for the construction of quaternary carbon centers bearing a nitrogen substituent has been rarely explored. To the best of our knowledge, Kotsuki et al have been the only to report the synthesis of a single product of β -amino ketones bearing heterocyclic-substituted quaternary centers via the addition of a triazole to a 3-methylcyclohex-2-enone under high-pressure and high-temperature conditions (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%